Effect of lens care systems on silicone hydrogel contact lens hydrophobicity - Lira, Madalena (2017)
Purpose: To analyze changes in wettability of hydrogel and silicone hydrogel contact lenses (CLs) when preserved in different lens care systems. Methods: In this research, four silicone hydrogel CLs (senofilcon A, balafilcon A, comfilcon A, and lotrafilcon B) and one conventional CL (etafilcon A) and appropriate lens care solutions (ReNu MultiPlus, Biotrue, OPTI-FREE PureMoist, and AOSept Plus) were used. Lenses were immersed in each lens care system for 12 hr and then CL hydrophobicity was determined through water contact angle (CA) measurements using the OCA 20 instrument (DataPhysics). Results: Mean CA values obtained when CLs were removed from blisters (baseline value) were lower for etafilcon A (49.6°63.0°) and comfilcon A (48.0°62.8°) and higher for senofilcon A (78.9°62.5°), lotrafilcon B (82.6°61.7°), and balafilcon A (91.5°60.7°). Depending on CL and lens care combination, it was detected a statistically significant reduction by 70% of the 20 combinations studied and any significant increase in the CA. When compared to baseline values, CA varied between etafilcon A: 2° and 11°, comfilcon A: 1° and 7°, senofilcon A: 2° and 28°, lotrafilcon B: 14° and 31°, and balafilcon A: 18° and 29°. Comfilcon A was the most stable lens material presenting only one significant decrease in CA. Conclusions: This study reveals the existence of interactions between CL material and lens solutions that can play an important role in CL surface wettability. The major changes were obtained in lenses with higher baseline CA, which showed significant changes with each of the solutions. These differences can be positive, because in almost all of the combinations, the lenses became more wettable.